Acetylcholine Receptors of Muscle Grown In Vitro - Vogel, Z. (1972)
[(125)I]Monoiodo- and [(125)I]diiodo-α-bungarotoxin were synthesized and shown to bind specifically to the acetylcholine receptor of cultured embryonic chick- and rat-muscle cells. The pharmacologic properties of the receptor of cultured embryonic chick muscle resembled those of the nicotinic acetylcholine receptor of adult vertebrate muscle. Autoradiography of muscle cells labeled with toxin showed that acetylcholine receptors were distributed over the entire cell surface. In addition, discrete areas with a high receptor concentration were found.